Holistic and Ecological Approach to Talent Development : A Turkish Volleyball Setting - Kiper, Sarp (2024)
The holistic and ecological approach in talent development in sports underscores the significant influence of the overall environment on an athlete’s journey of athletic growth. This framework was proposed to account for the environment and the holistic nature of athletic talent development shifting the focus away from individual athletes. Previous research in different sports has explored successful environments from a holistic and ecological perspective. It is suggested that successful talent development environments are those that achieve high levels of accomplishment in producing senior athletes from among their youth teams. These studies indicated that while successful environments are unique, they also possess common success factors in transitioning developing athletes to the elite level. This case study examined the athletic talent development of male and female athletes in a Turkish volleyball club, namely Arkas SK. The club has a successful track record in transitioning academy players to senior professional volleyball. The primary methods for data collection include observing participants in their daily environment, conducting interviews, and analyzing relevant documents. The environment of Arkas SK revolved around the interaction between the developing athletes and a team of coaches, staff members, and managers guiding players in their athletic journeys, balancing dual careers in sport and academics, and fostering accountability for training and respect for others. The results indicate that the environment shares many key features with successful environments observed in other sports such as ‘support for psychosocial development’ and ‘proximal role models.’ Results suggest that the case of Arkas SK with a new high intensity sport and geography, not only shares previously identified features with successful environments from other sports, but also provides new examples and perspectives to the shared features of successful and unique environments. In turn showing the wider generalizability and applicability of Holistic and Ecological Approach in different geographies and cultures.